Particulate matter air pollution and its relationship with respiratory type diseases in the population of Cerro de Pasco (2010 & 2016) - Robles Morales, Eder Guido (2019)
Beginning in the 17th century, mineral deposits of lead, copper, zinc and silver were discovered in Cerro de Pasco, Peru, which gave rise to a process of mining exploitation in that area. From that moment, the population in the vicinity of the mining activities began to principally suffer from acute respiratory infectious diseases. This study aims to determine the relationship between particulate matter smaller than 10 microns, generated during mining operations, and acute respiratory infections that affected the inhabitants of Cerro de Pasco in 2010 and 2016. To this end, the results from four particulate matter monitoring stations, the number of hospital admissions and the dry season were considered. This is a non-experimental and correlational study that considered a sample of 10 029 hospital admissions of patients aged five years old or younger and adults over 50 years old. Correlation coefficients of 0.36, p=0.415 and 0.60, p=0.00 with a 95% confidence interval were determined for the year 2010 and 2016, respectively. Finally, the result demonstrated that a significant relationship exists between particulate matter smaller than 10 microns produced by the sources of pollution and acute respiratory infectious diseases.